EXTRA-CAMPUS ORGANIZATIONAL STRATEGY: A CASE STUDY OF HIMMAH - Dwi Khairunnisa; Winda Cantika Ismajayanti Nasution; Junaidi (CENDEKIA INDONESIA, 2025)
This research aims to describe the Organizational Planning Process, both strategic and human resources in the scope of extra-campus organizations. This research is a qualitative type with an interview method. Data was obtained from sources related to the Himmah organization by recording voice and writing. Data was analyzed using direct question and answer sessions. The research results show that planning is a process systematically prepare the activities that will be carried out to achieve a goal. Based on analysis, planning is said to be a design carried out to achieve proper goals.